Operational Model and Tools for Studying Subjective Well-Being of Orphans and Children Without Parental Care - Oslon V.N; Semya G.V; Prokopeva L.M; Kolesnikova U.V (Moscow State University of Psychology and Education, 2020)
The article presents the rationale for the theoretical construct 'subjective well-being of orphans', its operational model, as well as the reliability and validity of a specially designed standardized interview (SI) for measuring and assessing both the general level of subjective well-being and its specific areas (SWB).The subjective well-being of a child is viewed from the position of his/her satisfaction with the 'system of own attitudes' to himself, to others, to the environment, to his/her 'chronotope'.The operational assessment model built on its basis included 10 domains that built the basis of SI. The tool was tested on a sample of 498 orphanage residents aged 13 to 17 years. Its reliability, internal consistency, correctness and validity have been proven: meaningful, constructive (Cronbach's coefficient "α" α k = 0.741); convergent (at the level of high statistical significance, SI indicators correlate with the method of M. Rosenberg, as well as with the results of the "Vi ability" test (Osin E.N., Rasskazova E.I., screening version); criterial (correlation analysis revealed the stable relationships between indicators of subjective well-being and institutional experience (r = 0.017, p = 0.702).